A kinetic analysis of leaf uptake of COS and its relation to transpiration, photosynthesis and carbon isotope fractionation - U. Seibt; J. Kesselmeier; L. Sandoval-Soto; U. Kuhn; J. A. Berry (Biogeosciences, 2010)
Carbonyl sulfide (COS) is an atmospheric trace gas that holds great promise for studies of terrestrial carbon and water exchange. In leaves, COS follows the same pathway as CO2 during photosynthesis. Both gases are taken up in enzyme reactions, making COS and CO2 uptake closely coupled at the leaf scale. The biological background of leaf COS uptake is a hydrolysis reaction catalyzed by the enzyme carbonic anhydrase. Based on this, we derive and test a simple kinetic model of leaf COS uptake, and relate COS to CO2 and water fluxes at the leaf scale. The equation was found to predict realistic leaf COS fluxes compared to observations from field and laboratory chambers. We confirm that COS uptake at the leaf level is directly linked to stomatal conductance. As a consequence, the ratio of normalized uptake rates (uptake rates divided by ambient mole fraction) for leaf COS and CO2 fluxes can provide an estimate of Ci/Ca, the ratio of intercellular to atmospheric CO2, an important plant gas exchange parameter that cannot be measured directly. The majority of published normalized COS to CO2 uptake ratios for leaf studies on a variety of species fall in the range of 1.5 to 4, corresponding to Ci/Ca ratios of 0.5 to 0.8. In addition, we utilize the coupling of Ci/Ca and photosynthetic 13C discrimination to derive an estimate of 2.8±0.3 for the global mean normalized uptake ratio. This corresponds to a global vegetation sink of COS in the order of 900±100 Gg S yr−1. COS can now be implemented in the same model framework as CO2 and water vapour. Atmospheric COS measurements can then provide independent constraints on CO2 and water cycles at ecosystem, regional and global scales.